Theoretical Calculation and Conformational Analysis of 3,5,7-Triphenyl-1-oxa-3,5,7-triazacyclooctane - Kakanejadifard, Ali; Zabardasti, Abedin; Kakanejadifard, Hadis (Asian Journal of Chemistry, 2010)
The energy of various conformers of eight membered ring molecule 3,5,7-triphenyl-1-oxa-3,5,7-triazacyclooctane (2a) have been calculated. The calculations were performed for HF/3-21+G(d,p) optimized geometries. The calculated energies indicate that saddle family (SF1) and crown family (CF) conformers are more stable than both-chair (BC), SF2 and SF3 conformers. The results of the calculations provide a clear picture of expected energetic differences in conformers and will be useful in both instruction and synthetic planning.